2020
DOI: 10.17559/tv-20190225122204
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Polyamide PA 2200 in SLS Technology

Abstract: Mechanical properties, accuracy and tribological properties of additively manufactured models depend on the technological parameters. In the presented work, models made in selective laser sintering technology with modified technological parameters were analyzed.Therefore, the presented research attempts to determine the influence of two technological parameters (layer thickness in the 0.1-0.4 mm range and the printing direction (0° and 90°)) on stress relaxation determined during the uniaxial compression test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Thus, FDM technology has been widely deployed in many industrial sectors, due to not only the aforementioned advantages but also the ease to post process FDM-printed components, e.g., heat treatment, chemical treatment [6], machining [7,8], polishing, painting or coating. Considering the material modification for FDM, materials enriched with additives are becoming very popular, allowing for better mechanical properties, such as: additives that can reduce the hardness to even 30 on the Shore scale, flame retardant additives (aviation Polymers 2021, 13, 1671 2 of 17 industry application), additives increasing mechanical properties, such as carbon fibers and glass fibers, and additives that enable the conduction of electricity and have magnetic properties. Specifically, the addition of glass and carbon fibers [9] seems very interesting, due to the fact that the process of building models using this material requires only a slightly higher temperature in the printing head extruder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, FDM technology has been widely deployed in many industrial sectors, due to not only the aforementioned advantages but also the ease to post process FDM-printed components, e.g., heat treatment, chemical treatment [6], machining [7,8], polishing, painting or coating. Considering the material modification for FDM, materials enriched with additives are becoming very popular, allowing for better mechanical properties, such as: additives that can reduce the hardness to even 30 on the Shore scale, flame retardant additives (aviation Polymers 2021, 13, 1671 2 of 17 industry application), additives increasing mechanical properties, such as carbon fibers and glass fibers, and additives that enable the conduction of electricity and have magnetic properties. Specifically, the addition of glass and carbon fibers [9] seems very interesting, due to the fact that the process of building models using this material requires only a slightly higher temperature in the printing head extruder.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the addition of glass and carbon fibers [9] seems very interesting, due to the fact that the process of building models using this material requires only a slightly higher temperature in the printing head extruder. As a matter of fact, glass and carbon fibers are very widely used in selective laser sintering (SLS) technology, where its addition improves the properties in such a way that it not only increases the strength of the manufactured models but also reduces the phenomenon of anisotropy of mechanical properties (especially in rheological tests) and accuracy, which is particularly visible in the production of thin-walled elements [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial for 3D printing production of high-quality models expressed by dimensional and shape accuracy, surface texture parameters, mechanical strength, abrasive wear resistance, etc., to consider the so-called process-control [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Process-control takes into account the analysis of many technological parameters depending on the 3D printing technology, such as: thickness of the fabricated layer, temperature of the build chamber, speed and power of the laser, diameter of the focused beam, printing nozzle diameter, format and accuracy of the digital file before printing, and many other parameters with a direct impact on the quality of the fabricated model.…”
Section: Introductionmentioning
confidence: 99%
“…Compressive stress relaxation tests within a uniaxial compression tests on models made using various (selected) polymer materials in FDM, PJM and SLS technologies were shown in selected publications [4,[38][39][40][41][42]. These tests showed that mechanical properties of the prepared models depended on preset process parameters, such as printed layer thickness and model orientation relative to the building platform, so-called "printing direction", as well as SLS laser operating parameters.…”
Section: Introductionmentioning
confidence: 99%